Dissociation among preserved resistance to proactive interference and impaired behavioral inhibition in a patient with bilateral lesions in the inferior frontal gyrus: A single-case study. (October 2019) - Loosli, Sandra V.; Bormann, Tobias; Mader, Irina; Martin, Markus; Schumacher, Lena V.; Katzev, Michael; Weiller, Cornelius; Kaller, Christoph P.
Abstract: Inhibition is not a unitary construct, as different inhibition-related functions have been disentangled. The present single-case study compares performance of a patient with bilateral lesions in the inferior frontal gyrus (IFG) and anterior insula to healthy age-matched controls in different inhibition-related tasks. Particular focus was on the resolution of proactive interference that is supposed to rely on bilateral IFG and anterior insula. Two working memory tasks previously proven sensitive to deficits in proactive interference (recent-probes, n -back) and two tasks measuring behavioral inhibition (verb generation task, Stroop task) were administered. Against expectations, the patient did not show any deficits in measures of proactive interference. However, compared to controls, she demonstrated considerably reduced performance in both measures of behavioral inhibition, thus resulting in a classical dissociation between proactive interference and behavioral inhibition. Although performance improved during the chronic phase post stroke, the overall pattern of a classical dissociation between proactive interference and behavioral inhibition remained stable across time. Taken together, the present data support the role of the IFG in inhibition-related functions, but a direct relationship between lesions in the IFG and difficulties in resolution of proactive interference could not be corroborated.